Investigations on the aging of ZnON thin film transistors and the effect of annealing on device performance - Vidhya V P; Parvathy Premlal; Priyanka K M; Raghu Chatanathodi; Venu Anand (Materials Research Express, 2025)
This study investigates the aging effects of zinc oxynitride (ZnON) thin-film transistors (TFTs) and the effect of annealing under different environments on the device performance. The temporal degradation of these TFTs is attributed to nitrogen desorption and adsorption of ambient species. Analytical characterization of ZnON thin films and DFT simulations reveal that only a weak bond exists between nitrogen and the ZnO matrix, indicative of physisorption rather than strong chemical adsorption. Post-deposition annealing of the devices slows the aging under certain conditions. The device parameter, like field effect mobility, shows nominal improvement due to annealing (2.29 cm ^2 V ^−1 s ^−1 to 7.39 cm ^2 V ^−1 s ^−1 ).